The Non-pharmacological treatment of chronic insomnia review - Rudzka, Aleksandra; Madejska, Maria Anna; Drzewiecka, Antonina; Drzewiecki, Artur; Korczak, Wiktor; Gaszyńska, Monika; Falkowski, Wojciech; Krysińska, Anna; Woźniak, Weronika; Magielski, Jakub (Journal of Education, Health and Sport, 2025)
Chronic insomnia is a sleep disorder defined by the presence of difficulty initiating or maintaining sleep, or early morning awakening and being unable to return to sleep, occurring at least three times per week for a duration of three months or more. This condition is associated with significant daytime functional impairment or distress, including fatigue, mood disturbances, and cognitive deficits. The aim of this article is to present the non-pharmacological methods of treatment of chronic insomnia. This type of therapy includes elements such as: Cognitive Behavioral Therapy for Insomnia (CBT-I), which incorporates strategies such as: sleep restriction, stimulus control, cognitive restructuring, sleep hygiene and relaxation techniques; Mindfulness-Based Cognitive Therapy (MBCT) and acupuncture. CBT-I have emerged as the gold standard for long-term management.